NILAI PENDIDIKAN AL-QUR'AN TENTANG MAAF DALAM FILM ANIMASI NUSA DAN RARA EPISODE MAAF - Aisyah, Rusnah (As-Syifa: Journal of Islamic Studies and History, 2025)
ABSTRACT The cultivation of ethical values from a formative age is the main foundation in the development of a child's character. Islamic pedagogy occupies an important position in this endeavor, especially through the moral and spiritual values derived from the Qur'an and Sunnah. The purpose of this study was to conduct an analysis of the depiction of the concept of forgiveness in two episodes of the animated series Nussa and Rara, specifically titled Sorry Part 1 and Sorry Part 2. Using qualitative methodology and library research techniques, content analysis was performed on dialogue and narrative structure to discern the values of Islamic moral education presented. Research findings show that these animations masterfully articulate ethical messages regarding the importance of holding back anger, seeking forgiveness, and forgiving the transgressions of others. These values are exemplified in depth through the strengthening of Quranic verses, including Surah Ali Imran verse 134, Al-Baqarah verse 237, and Ash-Shura verse 40. The evolution of Rara's character describes the process of internalizing Islamic principles through family guidance and social experience. These results underscore the great potential of animated media as a relevant and contextual source of nonformal education in cultivating the Islamic character of children in an increasingly digital era. ABSTRAK Kultivasi nilai-nilai etika dari usia formatif merupakan fondasi utama dalam pengembangan karakter anak. Pedagogi Islam menempati posisi penting dalam upaya ini, terutama melalui nilai-nilai moral dan spiritual yang berasal dari Al-Qur'an dan Sunnah. Tujuan dari penelitian ini adalah untuk melakukan analisis penggambaran konsep pengampunan dalam dua episode serial animasi Nussa dan Rara, yang secara khusus berjudul Maaf Bagian 1 dan Maaf Bagian 2. Menggunakan metodologi kualitatif dan teknik penelitian perpustakaan, analisis konten dilakukan pada dialog dan struktur naratif untuk membedakan nilai-nilai pendidikan moral Islam yang disajikan. Temuan penelitian menunjukkan bahwa animasi ini dengan mahir mengartikulasikan pesan etis mengenai pentingnya menahan amarah, mencari pengampunan, dan memaafkan pelanggaran orang lain. Nilai-nilai ini dicontohkan secara mendalam melalui penguatan ayat-ayat Al-Qur'an, termasuk Surah Ali Imran ayat 134, Al-Baqarah ayat 237, dan Asy-Syura ayat 40. Evolusi karakter Rara menggambarkan proses internalisasi prinsip-prinsip Islam melalui bimbingan keluarga dan pengalaman sosial. Hasil ini menggarisbawahi potensi besar media animasi sebagai sumber pendidikan nonformal yang relevan dan kontekstual dalam menumbuhkan karakter Islam anak-anak di era yang semakin digital.